Eldest - Paolini, Christopher (Barcelona : Rocabolsillo, 2010)
After successfully evading an Urgals ambush, Eragon and his dragon Saphira are adopted into the Ingeitum clan and sent to finish his training in magic and sword fighting so he can further help the Varden in their struggle against the Empire.
Translation of: Eldest.
Accelerated Reader AR
In Spanish.
Keywords: Imaginary places -- Juvenile fiction; Dragons -- Fiction; Youths' writings; Spanish language materials -- Fiction; Fantasy fiction